The HIF-prolyl hydroxylases have distinct and nonredundant roles in colitis-associated cancer - Kennel, Kilian; Burmeister, Julius; Radhakrishnan, Praveen; Giese, Nathalia; Giese, Thomas; Salfenmoser, Martin; Gebhardt, Jasper M.; Strowitzki, Moritz; Taylor, Cormac T.; Wielockx, Ben; Schneider, Martin; Harnoß, Jonathan M. (JCI insight, 2022)
Here, we investigated the importance of PHD1-3 in an azoxymethane- (AOM-) and dextran sodium sulfate-induced (DSS-induced) mouse model of CAC. Moreover, to gain a deeper understanding of the specific role of PHD2 - the key oxygen sensor (25) - in the pathogenesis of CAC, we used transgenic mouse models harboring a tissue-specific deletion of Phd2. We demonstrate that the 3 PHD isoenzymes have distinct, whether promoting (PHD1), diminishing (PHD2), or neutral (PHD3), effects on CAC growth in the AOM/DSS model.
Gesehen am 24.01.2023